7x + 9y = - 27_________eq1 3x - y = 3__________eq2 Multiply eq 2 by 9 and then add the resulting eq with eq1.
eq2 x 9 gives us 27x - 9y = 27___________eq3
add eq3 with eq1 we get. 34x = 0. where x=0/34 x=0. substitute x into any of the above equations to get y. substitute x into eq1. we get: 7(0) + 9y =-27 9y = -27 y= -27/9 y = -3.
So in order to use the substitution method, you rearrange one to have a variable isolated, so i isolated y. Then you plug in and solve for the other variable, then plug in that to an equation to find the remaining variable.